A design science approach to mixed-methods evaluation in serious game research - Luis Demetrio Gómez García; Gloria María Zambrano Aranda; Emerson Jesus Toledo Concha (MethodsX, 2025)
For a serious game to be effective, it must undergo rigorous validation process. A Design Science approach advocates the use of quantitative or qualitative research methodologies within the creation and validation of artifacts, an approach suitable for evaluating serious games as educational tools.This study presents a methodological framework that integrates quantitative measurement and qualitative inquiry to assess the effectiveness of a serious game designed for ethics education. We provide access to the quantitative questionnaire, its codebook, and the dataset generated during the validation of the authors’ approach using a serious game for teaching business ethics.The integration of both methods allowed us to validate the game as a relevant and effective strategy for promoting ethical reflection among university students. These findings support the consistency and reliability of the method used for validating serious games.Methodological Highlights • The quantitative assessment is based on the Technology Acceptance Model III (TAM III) and the Theory of Planned Behavior (TPB). • Qualitative inquiry analyzes students’ group work to understand their perceptions of ethical phenomena after gameplay. • Professors can use insights from students' perceptions as a starting point or framework for takeaways in future game applications.